The influence of experience economy and healthcare facility on intention of revisiting through patient satisfaction as an intervening variable - Murti, Oktavia Wahyu Krisna; Martini , Ni Nyoman Putu; Herlambang, Toni (Jurnal Ekonomi & Studi Pembangunan, 2025)
The development of the hospital service sector provides many choices of places for people to seek treatment. Hospitals have a duty to provide health services to the community on an ongoing basis. The purpose of this study is to test and analyze the effect of experience economy and healthcare facility on the intention of revisiting patients through patient satisfaction as an intervening variable (Study on Outpatients at Kalisat Regional Hospital). This study uses descriptive quantitative research. The population of this study were outpatients of the Kalisat Regional Hospital and sampling using purposive sampling method. The analysis technique used in hypothesis testing is Variance-based SEM or Partial Least Square (SEM-PLS) testing with the warp pls 7.0 program. The results showed that experience economy has a positive and significant effect on intention of revisiting and patient satisfaction. Healthcare facility has a positive and significant effect on intention of revisiting and patient satisfaction. Patient satisfaction has a positive and significant effect on intention of revisiting. Experience economy and healthcare facility have a positive and significant effect on intention of revisiting through patient sSatisfaction as an intervening variable.